Childhood obesity as a predictor of morbidity in adulthood: a systematic review and meta‐analysis. (6th October 2015) - Llewellyn, A.; Simmonds, M.; Owen, C. G.; Woolacott, N.
Summary: Obese children are at higher risk of being obese as adults, and adult obesity is associated with an increased risk of morbidity. This systematic review and meta‐analysis investigates the ability of childhood body mass index (BMI) to predict obesity‐related morbidities in adulthood. Thirty‐seven studies were included. High childhood BMI was associated with an increased incidence of adult diabetes (OR 1.70; 95% CI 1.30–2.22), coronary heart disease (CHD) (OR 1.20; 95% CI 1.10–1.31) and a range of cancers, but not stroke or breast cancer. The accuracy of childhood BMI when predicting any adult morbidity was low. Only 31% of future diabetes and 22% of future hypertension and CHD occurred in children aged 12 or over classified as being overweight or obese. Only 20% of all adult cancers occurred in children classified as being overweight or obese. Childhood obesity is associated with moderately increased risks of adult obesity‐related morbidity, but the increase in risk is not large enough for childhood BMI to be a good predictor of the incidence of adult morbidities. This is because the majority of adult obesity‐related morbidity occurs in adults who were of healthy weight in childhood. Therefore, targeting obesity reduction solely at obese or overweight children may not substantially reduce the overall burden of obesity‐related disease in adulthood.